Factors Affecting Employee Performance During the Covid Pandemic 19 - Bahagia, Rahmad; Putri, Linzzy Pratami (AIBPM Publisher, 2020)
This study aims to determine factors affecting employee performance of private companies in Medan City during the COVID-19 pandemic. The population in this study were all private employees in Medan City. The samples were selected accidental sampling technique. The research method used was descriptive quantitative with factor analysis techniques. The results of the study highlighted that there are two dominant factors which influence employee performance decisions during the Covid 19 pandemic, namely.